2008
DOI: 10.1242/jeb.015503
|View full text |Cite
|
Sign up to set email alerts
|

The correlated evolution of biomechanics, gait and foraging mode in lizards

Abstract: SUMMARYForaging mode has molded the evolution of many aspects of lizard biology. From a basic sit-and-wait sprinting feeding strategy, several lizard groups have evolved a wide foraging strategy, slowly moving through the environment using their highly developed chemosensory systems to locate prey. We studied locomotor performance, whole-body mechanics and gaits in a phylogenetic array of lizards that use sit-and-wait and wide-foraging strategies to contrast the functional differences associated with the need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 63 publications
1
25
0
Order By: Relevance
“…Huey and Hertz, 1984;Futuyma and Moreno, 1988). For varanid lizards, we were unable to find a strong relationship between foraging mode and limb kinematics, as has been reported previously (McElroy et al, 2008). However, we did find strong evidence for a difference in the determinants of speed between climbing and non-climbing lizards, with climbing lizards varying speed predominately by stride frequency and terrestrial lizards predominately by stride length, reflecting results seen in geckos (Zaaf et al, 2001).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Huey and Hertz, 1984;Futuyma and Moreno, 1988). For varanid lizards, we were unable to find a strong relationship between foraging mode and limb kinematics, as has been reported previously (McElroy et al, 2008). However, we did find strong evidence for a difference in the determinants of speed between climbing and non-climbing lizards, with climbing lizards varying speed predominately by stride frequency and terrestrial lizards predominately by stride length, reflecting results seen in geckos (Zaaf et al, 2001).…”
Section: Discussionsupporting
confidence: 81%
“…An analysis of spatio-temporal gait characteristics for two species of gecko, which differed in climbing ability, showed that the ground-dwelling species achieved high speeds by changing stride length, while the climbing species modified stride frequency (Zaaf et al, 2001). Further, in a phylogenetically diverse sample of lizards, there were patterns of covariation between foraging mode and locomotor mechanics, showing that widely foraging species used a slower vaulting gait, while sit-and-wait species used a faster bouncing gait (McElroy et al, 2008). By measuring differences in the kinematic movement of the hindlimb it is possible to infer and detect differences in whole-body performance variables that are difficult to measure directly (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true in species that do not routinely move at steady speed, which is true of many small sprawling animals (Reilly et al, 2007). For example, studies of ground reaction forces in lizards and other sprawling animals have used changes in speed anywhere from 5% to 50% as a criteria to define 'steady speed' locomotion (Full and Tu, 1991;Farley and Ko, 1997;Ahn et al, 2004;Autumn et al, 2006;Chen et al, 2006;Reilly et al, 2006;McElroy et al, 2008;McElroy and Reilly, 2009). In fact, the study of individual limb forces in the house gecko ) used a speed change of <15%, which was similar to our study.…”
Section: Discussionmentioning
confidence: 99%
“…First, we ensured that speed over any 10 cm interval as measured by digitizing the lizard's snout was <20% different than the average speed down the racetrack; by this definition the lizard moved with only small speed fluctuations down the entire surface of the force platform (see also McElroy et al, 2008;McElroy and Reilly, 2009). To further ensure that trials were at steady speed down the length of the force platform, we compared the magnitude of the braking versus accelerative impulse within each trial for the portion of the trial that included whole body forces (Fig.…”
Section: Research Articlementioning
confidence: 99%
“…In addition, we employed multiple regression to test for the relative effects of three independent variables on each kinematic variable: age, relative body (to substrate) size and (because there is ample evidence that speed influences many aspects of locomotor kinematics) Froude number. Because it is conventional to regress limb phase against duty factor, and duty factor has been shown to be correlated with limb phase (Cartmill et al, 2002;Lemelin et al, 2003;Hutchinson et al, 2006;Young et al, 2007;McElroy, 2008;Young, 2008), we also included duty factor as a fourth independent variable in the multiple regression for limb phase. Froude number has no significant effect on limb phase once duty factor is controlled for.…”
Section: Statistical Analysesmentioning
confidence: 99%